2020
DOI: 10.1364/oe.392358
|View full text |Cite
|
Sign up to set email alerts
|

Image reconstruction with a deep convolutional neural network in high-density super-resolution microscopy

Abstract: An accurate and fast reconstruction algorithm is crucial for the improvement of temporal resolution in high-density super-resolution microscopy, particularly in view of the challenges associated with live-cell imaging. In this work, we design a deep network based on a convolutional neural network to take advantage of its enhanced ability in high-density molecule localization, and introduce a residual layer into the network to reduce noise. The proposed scheme also incorporates robustness against variations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Similarly, numerous optimization scenarios within the optoelectronic system require optimization, such as adaptive optics and fiber coupling. Adaptive optics requires multidimensional optimization that can enable clear imaging in optoelectronic tracking systems, making image quality much better, and reducing the difficulty of target detection and target tracking algorithms [21]. Fiber-optic coupling is a simplified version of adaptive optics, and generally, needles are optimized in only two dimensions.…”
Section: Experimental Designmentioning
confidence: 99%
“…Similarly, numerous optimization scenarios within the optoelectronic system require optimization, such as adaptive optics and fiber coupling. Adaptive optics requires multidimensional optimization that can enable clear imaging in optoelectronic tracking systems, making image quality much better, and reducing the difficulty of target detection and target tracking algorithms [21]. Fiber-optic coupling is a simplified version of adaptive optics, and generally, needles are optimized in only two dimensions.…”
Section: Experimental Designmentioning
confidence: 99%
“…With the continuous development of imaging technology, perineotomy under the guidance of ultrasound images can not only show the layers of the tissues but also reduce the risk of pudendal nerve block [8]. Yao et al [9] reported that the use of an ultrasound probe to move along the pudendal nerve in the human body for translation can clearly show the pudendal nerve at all levels. Liu et al [10] proposed the fast super resolution reconstructed convolutional neural network (FSRCNN) algorithm in 2018. e network structure is improved.…”
Section: Introductionmentioning
confidence: 99%
“…CBV refers to the VOLUME of blood through a certain cross-section of cerebrovascular in a unit time, which can reflect the damage of brain tissue. 14 - 15 CBF refers to the total amount of blood contained in cerebral blood vessels (including cerebral arteries, arterioles, and capillaries), and it has important guiding value for the clinical treatment of patients with acute cerebral infarction. 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%